Translational analysis and final efficacy of the AVETUX trial – Avelumab, cetuximab and FOLFOX in metastatic colorectal cancer - Tintelnot, Joseph; Ristow, Inka; Sauer, Markus; Simnica, Donjete; Schultheiß, Christoph; Scholz, Rebekka; Goekkurt, Eray; von Wenserski, Lisa; Willscher, Edith; Paschold, Lisa; Lorenzen, Sylvie; Riera-Knorrenschild, Jorge; et al. (Frontiers in Oncology, 2022)
In metastatic colorectal cancer (mCRC), the efficacy of immune checkpoint blockade (ICB) has so far been limited to patients with microsatellite instability high tumors (MSI-H). Unfortunately, most mCRC patients suffer from non-immunogenic microsatellite stable (MSS) tumors. Therefore, new combinatorial strategies are urgently needed to enhance the immunogenicity of MSS tumors to finally increase the number of patients benefiting from ICB. The AVETUX trial aimed to combine the PD-L1 antibody avelumab with the standard of care chemotherapy combination FOLFOX and the anti-EGFR antibody cetuximab. In total, 43 patients were treated of which 39 patients were confirmed as RAS/BRAF wt wildtype in central tissue review and finally response evaluated. A final progression-free survival (PFS) of 11.1 (range: 0.8 to 22.3 months) and a herein updated final overall survival (OS) of 32.9 months (range: 0.8 to 47.1 months) was reached. Here, we performed a central radiological review of the pre- and on-treatment computed tomography scans to better define the individual response to treatment. We observed a strong median depth of response of 67.5% tumor shrinkage and deepness of response correlated significantly with survival. On the other hand, early tumor shrinkage was not an indicator of better outcome at a cut-off of 20% (median values). In a next step, we correlated the individual best radiological response with potential ICB response biomarkers and found that the clonality and diversity, but not frequency of tumor infiltrating lymphocytes (TiLs) and peripheral blood mononuclear cells (PBMCs), strongly correlated with response. In summary, we report the final overall survival of the AVETUX trial and propose T cell clonality and diversity as a potential marker to predict response to chemo-immunotherapy combinations in MSS mCRC by performing a central radiological review.